Reaching the Urban Poor with Private Infrastructure - Brook Cowen, Penelope; Tynan, Nicola (World Bank, Washington, DC, 2012)
Nontraditional infrastructure service providers supply many low-income consumers in slums and urban peripheries in developing countries. And technological change has eased entry by new providers. But the current approach to private participation in infrastructure typically gives exclusivity to a local monopoly for a long period. In return, the monopoly utility is obligated to provide service to all in the area at a certain standard, charging a rising block tariff and using some cross-subsidies. This approach can inadvertently erect barriers to improving service for low-income households. Policymakers therefore need to rethink their approach to private participation transactions and their regulation. In particular, they need to focus on facilitating new entry.